The right of self-determination of peoples the domestication of an illusion - Fisch, Jörg 1947- (Human rights in history, 2015)
The right of self-determination of peoples holds out the promise of sovereign statehood for all peoples and a domination-free international order. But it also harbors the danger of state fragmentation that can threaten international stability if claims of self-determination lead to secessions. Covering both the late eighteenth- and early nineteenth-century independence movements in the Americas and the twentieth-century decolonization worldwide, this book examines the conceptual and political history of the right of self-determination of peoples. It addresses the political contexts in which the right and concept were formulated and the practices developed to restrain its potentially anarchic character, its inception in anti-colonialism, nationalism, and the labor movement, its instrumentalization at the end of the First World War in a formidable duel that Wilson lost to Lenin, its abuse by Hitler, the path after the Second World War to its recognition as a human right in 1966, and its continuing impact after decolonization